2010
DOI: 10.1038/nchem.629
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anhydrous proton transport by supramolecular nanochannels in comb polymers

Abstract: Transporting protons is essential in several biological processes as well as in renewable energy devices, such as fuel cells. Although biological systems exhibit precise supramolecular organization of chemical functionalities on the nanoscale to effect highly efficient proton conduction, to achieve similar organization in artificial systems remains a daunting challenge. Here, we are concerned with transporting protons on a micron scale under anhydrous conditions, that is proton transfer unassisted by any solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 36 publications
5
113
0
1
Order By: Relevance
“…The mechanism of PT in aqueous systems has been extensively studied and is well understood. In contrast, the PT mechanisms under anhydrous conditions appear to depend on the material and are a matter of debate [5][6][7][8]. This work provides atomic-level insight into how PT takes place on OH-functionalized graphane and why the barriers to PT on this material are so low.…”
mentioning
confidence: 94%
“…The mechanism of PT in aqueous systems has been extensively studied and is well understood. In contrast, the PT mechanisms under anhydrous conditions appear to depend on the material and are a matter of debate [5][6][7][8]. This work provides atomic-level insight into how PT takes place on OH-functionalized graphane and why the barriers to PT on this material are so low.…”
mentioning
confidence: 94%
“…This example suggested that supramolecular organization is crucial in obtaining efficient proton transport. [7] To achieve a highly organized structure of aromatic cores of discotic columnar liquid crystals, support with nanoconfinements was used.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We succeeded in obtaining proton conductivity of 4.7 × 10 −3 S cm −1 at 200 ‱ C in the layered side-chain liquid crystal polymers bearing sulfonic acids [11]. Styrenic comb polymers self-assembling into supramolecular structures with cylindrical imidazole-rich domains showed proton conductivity of 10 −3 S cm −1 at 200 ‱ C [12]. Proton conduction in these supramolecular self-assemblies occurred by successive proton transfers along the ordered hydrogen bond networks.…”
Section: Introductionmentioning
confidence: 93%